AI Model for Improving Social Protection Delivery in Zambia - Muzungaile , Farai; Njovu, Chiyaba (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
Social Protection programmes in Zambia aim to reduce the levels of poverty and improve the lives of the vulnerable in the communities. However, the two most common challenges in the Social Protection sector in Zambia are fragmented data and poor targeting of beneficiaries. This report describes the development of an AI model prototype for improving Social Protection delivery in Zambia. AI models such as machine learning are discussed in helping solve the fragmented data problem through integration of data from different management information systems as well as improve the targeting challenge using algorithms. The legal, technological and ethical issues in relation to the prototype being developed are also discussed. Furthermore, the report discussed the future works on the enhancements of the model and its functionality.